Managing iron supply during the infection cycle of a flea borne pathogen, Bartonella henselae - Biville, Francis; Liu, Ma Feng (Frontiers in Cellular and Infection Microbiology, 2013)
Bartonella are hemotropic bacteria responsible for emerging zoonoses. Most Bartonella species appear to share a natural cycle that involves an arthropod transmission, followed by exploitation of a mammalian host in which they cause long-lasting intra-erythrocytic bacteremia. Persistence in erythrocytes is considered an adaptation to transmission by bloodsucking arthropod vectors and a strategy to obtain heme required for Bartonella growth. Bartonella genomes do not encode for siderophore biosynthesis or a complete iron Fe3+ transport system. Only genes, sharing strong homology with all components of a Fe2+ transport system, are present in Bartonella genomes. Also, Bartonella genomes encode for a complete heme transport system. Bartonella must face various environments in their hosts and vectors. In mammals, free heme and iron are rare and oxygen concentration is low. In arthropod vectors, toxic heme levels are found in the gut where oxygen concentration is high. Bartonella genomes encode for 3–5 heme-binding proteins. In Bartonella henselae heme-binding proteins were shown to be involved in heme uptake process, oxidative stress response, and survival inside endothelial cells and in the flea. In this report, we discuss the use of the heme uptake and storage system of B. henselae during its infection cycle. Also, we establish a comparison with the iron and heme uptake systems of Yersinia pestis used during its infection cycle.